2015
DOI: 10.1097/ana.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Heart Rate Variability to Acute Pain After Minor Spinal Surgery

Abstract: This study suggests that, after MSS, values of LF>298 m and LF/HF>3.1 denote acute pain (NRS>3). These HRV parameters are significantly correlated with NRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 51 publications
1
42
2
Order By: Relevance
“…Increase in the pain level leads to increases in blood pressure, heart rate, and respiratory rate. [ 10 12 13 21 ] This finding confirms the effect of catecholamine releasing and its positive impact on the quality of pain such as inotropic, chronotropic, and dromotropic effects on the heart rate and respiratory rate. Systolic blood pressure subsequently increased.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increase in the pain level leads to increases in blood pressure, heart rate, and respiratory rate. [ 10 12 13 21 ] This finding confirms the effect of catecholamine releasing and its positive impact on the quality of pain such as inotropic, chronotropic, and dromotropic effects on the heart rate and respiratory rate. Systolic blood pressure subsequently increased.…”
Section: Discussionsupporting
confidence: 65%
“…[ 9 ] In a parallel manner, activation of the sympathetic system and catecholamine release due to pain cause to increases blood pressure, heart rate, and respiratory rate, and decreases respiratory volume (with a greater impact on tidal volume) and finally myocardial infarction. [ 10 11 12 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…On full-text review, 14 studies were excluded and 8 studies fulfilled the inclusion criteria. 9 , 10 , 13 , 38 , 40 , 55 , 66 …”
Section: Resultsmentioning
confidence: 99%
“…All the included studies used a prospective observational study design. 9 , 10 , 13 , 38 , 40 , 55 , 66 A summary of the study features is shown in Table 1 . The studies analyzed data from a total of 1002 participants undergoing noncardiac surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, HRV analysis has been examined as one of the main ways to measure pain in different types; in Sesay et al [ 24 ], for instance, with the majority of 120 patients, it was observed that regarding acute pain after minor surgery, NRS was correlated with low-frequency (LF) band and the ratio of LF to high-frequency (HF) band but not with HF. To monitor the nociception level of patients with multiple physiological parameters, HF in a 1-minute window was calculated in Ben-Israel et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%